OWNERSHIP STRUCTURE AND TAX AVOIDANCE: AUDIT QUALITY AS A MODERATION - Nurdiana, Salsabila Putri; Usnan, Usnan (Kesatuan Press, 2025)
In addition to examining the correlation between ownership structure and tax avoidance, this research further seeks to establish if audit quality can reinforce the effect of ownership structure on tax avoidance. The study examines manufacturing firms listed between 2019-2023 on the Indonesia Stock Exchange (IDX). Purposive sampling was employed, and 26 companies with 130 data points were selected based on a 5-year observation period (2019–2023). The analysis method employed is panel data regression utilizing the Eviews 10 software. The study's results indicate that while institutional ownership positively impacts tax avoidance, there is no correlation between tax avoidance and managerial and family ownership. While audit quality may enhance the impact of family and institutional ownership on tax avoidance, it cannot enhance the effect of management ownership on tax avoidance.